Jajanan Di Mata Mahasiswa Pada Aplikasi Gofood Studi Kasus: Mahasiswa STIEPAR API Yogyakarta - Nuviah Herawati; Koesharijadi; Yulianto Pudjiwinarno (Journal of Tourism and Economic, 2021)
This study aims to find out what factors encourage consumers to make purchasing decisions culinary products offered through the GoFood application. The research approach uses variables and dimensions of the marketing mix. The marketing mix studied are product, price, distribution and promotion. The study used quantitative methods with regression analysis. Respondents are students of the STIE Tourism API Yogyakarta campus in a certain research period for one month. The measuring instrument used is a questionnaire with the use of a Likert scale. Using the t test, it can be concluded that products and promotions have a significant effect on purchasing decisions through the GoFood application. While price and distribution have no significant effect on purchasing decisions, and with the F-test it is concluded that product, price, distribution, and promotion together have a significant effect on purchasing decisions through the GoFood application.